A Using Prezi in Improving Students’ Grammar: English - Septiana Wandira; Dwi Nur Hadiyansah; Siti Fitria; Aswifatul Mu’mina (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
This research was aimed at determining the use of Prezi in improving students’ grammar mastery. The research method was Classroom Action Research (CAR), which consisted of 2 cycles, each cycle including planning, implementing, observing, and reflecting. The data collection was pre-test and post-test. The result showed students’ increased learning outcomes in each cycle. The increase in learning was shown in the pre-test result with a percentage of learning completeness of 0%, and there was an increase in the post-test cycle from 1 to 59%, and it increased again in the results of the post-test cycle from 2 to 82%. The increase in learning outcomes from pre-test, post-test 1, and post-test 2 was due to improvements in the application of Prezi. It can be concluded that learning using Prezi in Grade IX SMP Plus Abdul Aziz can improve students’ grammar mastery.